2017
DOI: 10.1021/acsami.6b16856
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of {111} Facet-Exposed MgO with Surface Oxygen Vacancies for Reactive Oxygen Species Generation in the Dark

Abstract: Seeking a simple and moderate route to generate reactive oxygen species (ROS) for antibiosis is of great interest and challenge. This work demonstrates that molecule transition and electron rearrangement processes can directly occur only through chemisorption interaction between the adsorbed O and high-energy {111} facet-exposed MgO with abundant surface oxygen vacancies (SOVs), hence producing singlet oxygen and superoxide anion radicals without light irradiation. These ROS were confirmed by electron paramagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 55 publications
4
82
0
Order By: Relevance
“…The results indicate that O 2 •− was not apparently involved in O 3 alone but was one of the ROS in each of the MgO/O 3 processes. By comparisons, it was found that the formation of O 2 •− was due to the existence of MgO, which was also reported by others . Hao et al .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The results indicate that O 2 •− was not apparently involved in O 3 alone but was one of the ROS in each of the MgO/O 3 processes. By comparisons, it was found that the formation of O 2 •− was due to the existence of MgO, which was also reported by others . Hao et al .…”
Section: Resultssupporting
confidence: 81%
“…Hao et al . proved that superoxide anion radicals could be produced on the surface of MgO in the molecule transition and electron rearrangement processes, which occurred through the interaction between the chemisorbed O 2 and the MgO with abundant surface oxygen vacancies (SOVs) without light irradiation . Based on the above results, it is deduced that MgO enhances O 3 mass transfer from gas to liquid phase by promoting the decomposition of aqueous O 3 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Optical investigations can reveal very useful information to understand the physical properties of materials [23,49]; as a result, photoluminescence spectroscopy (PL) of three kinds of MgO with different particle sizes are given in Figure 8. With an excitation wavelength of 325 nm, the PL spectra exhibit an intrinsic emission peak at 372 nm, a purple emission resulted from adsorbed oxygen species centered around 400 nm, and two blue emission around 454 and 469 nm, which are attributed to the oxygen vacancy (F center) [50,51]. When the valence band of MgO is excited by light, some of photogenerated electrons are trapped by oxygen vacancies.…”
Section: Effect Of Hydroxyl and Oxygen Vacancy In The Mgo Surface On mentioning
confidence: 99%
“…15 However, in these synthetic procedures, 9,10,15 researchers have paid less attention to the crystal facet of nano MgO; MgO usually grows into a cubic structure with (100) facets. 16 In the past few years, numerous studies have focused on MgO with the (111) polar facet due to its higher reactivity in catalysis 17,18 and antibacterial 19 applications. However, the reports about nano MgO with (111) polar facets and its properties are rare.…”
Section: Introductionmentioning
confidence: 99%